CRISPR-Cas9-mediated pinpoint microbial genome editing aided by target-mismatched sgRNAs - Lee, Ho Joung; Kim, Hyun Ju; Lee, Sang Jun (Genome Research, 2020)
Genome editing has been revolutionized by the CRISPR-Cas9 system. CRISPR-Cas9 is composed of single-molecular guide RNA (sgRNA) and a proteinaceous Cas9 nuclease, which recognizes a specific target sequence and a protospacer adjacent motif (PAM) sequence and, subsequently, cleaves the targeted DNA sequence. This CRISPR-Cas9 system has been used as an efficient negative-selection tool to cleave unedited or unchanged target DNAs during site-specific mutagenesis and, consequently, obtain microbial cells with desired mutations. This study aimed to investigate the genome editing efficiency of the CRISPR-Cas9 system for in vivo oligonucleotide-directed mutagenesis in bacteria. This system successfully introduced two- to four-base mutations in galK in Escherichia coli with high editing efficiencies (81%−86%). However, single-point mutations (T504A or C578A) were rarely introduced with very low editing efficiencies (<3%), probably owing to mismatch tolerance. To resolve this issue, we designed one- or two-base mismatches in the sgRNA sequence to recognize target sequences in galK in E. coli. A single-point nucleotide mutation (T504A or C578A in the galK gene) was successfully introduced in 36%−95% of negatively selected E. coli cells using single-base mismatched sgRNAs. Sixteen targets were randomly selected through genome-wide single-base editing experiments using mismatched sgRNAs. Consequently, out of 48 desired single-base mutations, 25 single bases were successfully edited, using mismatched sgRNAs. Finally, applicable design rules for target-mismatched sgRNAs were provided for single-nucleotide editing in microbial genomes.
10.1101/gr.257493.119